Wave-DNA: A software tool for simulating nonlinear acoustic waves emitted by moving boundaries - Sören Schenke; Fabian Sewerin; Berend van Wachem; Fabian Denner (SoftwareX)
The investigation of nonlinear acoustics requires sophisticated and tailored methods to advance the state of the art. Here we present the software tool Wave-DNA for the simulation of nonlinear acoustic waves emitted by stationary or moving boundaries in quiescent or moving fluids, assuming a one-dimensional or spherically-symmetric geometry. At its core, Wave-DNA is based on the convective Kuznetsov equation, a second-order nonlinear acoustic wave equation that accounts for the background flow and may be reduced to alternative wave equations by applying simplifying assumptions. A tailored finite-difference time-domain method with time-dependent coordinate transformation enables the accurate simulation of acoustic waves emitted by moving boundaries.